2012
DOI: 10.1016/j.neuint.2011.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Riluzole elevates GLT-1 activity and levels in striatal astrocytes

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 55 publications
2
78
0
1
Order By: Relevance
“…EAAT2 upregulation, we note that not all studies have confirmed that EAAT2 can be upregulated by ceftriaxone (39,40). Similarly, our study found only marginal upregulation of EAAT2 with ceftriaxone administration to mice ( Figure 3F).…”
Section: Methodssupporting
confidence: 59%
“…EAAT2 upregulation, we note that not all studies have confirmed that EAAT2 can be upregulated by ceftriaxone (39,40). Similarly, our study found only marginal upregulation of EAAT2 with ceftriaxone administration to mice ( Figure 3F).…”
Section: Methodssupporting
confidence: 59%
“…3 and 4). 4,31,40 Even though studies have demonstrated that riluzole can upregulate GLT-1 on cultured astrocytes, 3,22 even in the absence of neurons, 8 riluzole does not alter the expression of striatal GLT-1 in a rodent model of Parkinson's disease when given at a dosage (4 mg/kg) comparable to that used here. 9 Therefore, it can be hypothesized that upregulation of spinal GLT-1 with riluzole treatment after a painful nerve root com- pression is likely a secondary mechanism of its neuroprotective properties (Figs.…”
Section: Discussionmentioning
confidence: 62%
“…Riluzole upregulates GLT-1 levels and activity in cultured primary mouse striatal astrocytes, independent of actions on ion channels [142]. In one study, cultured C6 astroglial cells were used to examine three independent intracellular pathways of glutamate metabolism, confirming that riluzole stimulates glutamate uptake and is an enhancer of EAAT1, dependent on the PKC, fibroblast growth factor receptor (FGFR) and phosphatidylinositol 3-kinase (PI3K) pathways [143].…”
Section: +mentioning
confidence: 99%